(untitled) (GEOmedia, 2010)
A GIS for pedestrian safety management The improvement of pedestrian safety can be pursued through an innovative management system that can drive them through the safest pedestrian footpaths. Thanks to the support of GIS, one can now project future scenarios where pedestrians are warned in real time about the network elements offering the best safety performance. In this paper the characteristics of a GIS created for the dynamic characterization of level of safety provided by walkways will be explained. All the elements of an urban road network have been linked with attributes used to define the level of safety. The query space allows to identify the safest pedestrian route between origin and destination choices. Selecting the best route, the GIS also impute any barriers in the network.